Kajian usability testing pada Perpustakaan Digital Universitas Diponegoro - Legstyanto, Syeh Johan; Ganggi, Roro Isyawati Permata (Al-Kuttab : Jurnal Kajian Perpustakaan, Informasi dan Kearsipan, 2025)
A digital library signifies the rapid development of technology in the library field. With the existence of a digital library, patrons are facilitated in accessing library services without the need to physically visit the library building. The ease of obtaining credible information is a advantage of digital libraries. This necessitates digital libraries to have a good level of usability so that users can satisfactorily utilize the digital library. The aim of this research is to determine the level of usability on the Digital Library of Diponegoro University. This research employs a quantitative research method with a descriptive statistical approach. Data collection techniques are conducted through questionnaires and literature study. Respondent selection in this research uses purposive sampling technique. The respondents in this study amounted to 40 (forty) individuals, consisting of lecturers, educational staff, and active students at Diponegoro University. Data analysis is conducted through several stages as outlined: tabulation, calculation of averages, and drawing conclusions. The research results indicate that the level of success in usability performance on the Digital Library of Diponegoro University can be considered successful. This is demonstrated by all the indicators that measure the usability level on the Digital Library of Diponegoro University, showing a range of average scores for each indicator, all of which are high, ranging from 2.69 to 3.06. The highest average score is obtained by the learnability indicator, which is 3.06, while the lowest average score is obtained by the errors indicator, which is 2.69.